2007
DOI: 10.1074/jbc.m703643200
|View full text |Cite
|
Sign up to set email alerts
|

Roles for Two Aminopeptidases in Vacuolar Hemoglobin Catabolism in Plasmodium falciparum

Abstract: During the erythrocytic stage of its life cycle, the human malaria parasite Plasmodium falciparum catabolizes large quantities of host-cell hemoglobin in an acidic organelle, the food vacuole. A current model for the catabolism of globin-derived oligopeptides invokes peptide transport out of the food vacuole followed by hydrolysis to amino acids by cytosolic aminopeptidases. To test this model, we have examined the roles of four parasite aminopeptidases during the erythrocytic cycle. Localization of tagged ami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

13
192
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 150 publications
(205 citation statements)
references
References 48 publications
13
192
0
Order By: Relevance
“…Whereas the precise functions of Pf A-M1 and Pf A-M17 are still speculative it is suggested that these enzymes function in the final stages of haemoglobin digestion and degrade the dipeptides produced by the action of various enzymes within the parasite's acidic digestive vacuole (4,5,7,8). This process is essential for the provision of free amino acids for parasite protein synthesis.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Whereas the precise functions of Pf A-M1 and Pf A-M17 are still speculative it is suggested that these enzymes function in the final stages of haemoglobin digestion and degrade the dipeptides produced by the action of various enzymes within the parasite's acidic digestive vacuole (4,5,7,8). This process is essential for the provision of free amino acids for parasite protein synthesis.…”
Section: Discussionmentioning
confidence: 99%
“…The consensus is that the Pf A-M17 is located within the cytosol of the parasite. However, while we (4) and others (11,12) have also located the Pf A-M1 within the cytosolic compartment by immunocytochemistry, Dalal and Klemba (2007), using immunocytochemistry, light microscopy and YFP-tagging, observed the enzyme in the acidic digestive vacuole and nucleus (8).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…1) that has been proposed to play an important role in the parasite's catabolism of host red blood cell hemoglobin in its food vacuole (2). In their report on PfA-M1, McGowan et al (3) claim to provide evidence that this enzyme is located in the parasite cytosol.…”
mentioning
confidence: 95%